Historical aspects of the creation of the first higher educational institution of industrial education of Volyn province (to the 100th anniversary of Zhytomyr Polytechnic) - V.V. Ievdokymov; O.V. Oliinyk; Morozov A.V.; A.O. Chagaida (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Historical aspects of the creation of the first higher educational institution of industrial education of Volyn province (to the 100th anniversary of Zhytomyr Polytechnic)